2021
DOI: 10.7717/peerj.11981
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration half-life of biodegradable plastic films on different marine beach sediments

Abstract: The seafloor is considered the major sink for plastic debris in the world’s oceans. Biodegradable polymers are available on the market as a substitute for conventional plastic and could potentially end up in the same environment. To gain more insight into the effects of different sediments on the degradation rate of biodegradable plastic we performed two iterative seawater tank experiments. First, to test the effect of sediment grain size, film of Mater-Bi HF03V, a blend of thermoplastic starch and biodegradab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Polyhydroxybutyrate (PHB) is known to be a biodegradable polymer and often serves as positive control in degradation experiments [16][17][18]. PHB samples were fabricated of the material P209 (Biomer, Schwalbach, Germany) by injection molding.…”
Section: Phb Plastic Samples Exposed To Marine Environmentmentioning
confidence: 99%
“…Polyhydroxybutyrate (PHB) is known to be a biodegradable polymer and often serves as positive control in degradation experiments [16][17][18]. PHB samples were fabricated of the material P209 (Biomer, Schwalbach, Germany) by injection molding.…”
Section: Phb Plastic Samples Exposed To Marine Environmentmentioning
confidence: 99%
“…(ii) Chain length: The chain length is related to the number of bonds to be hydrolyzed, the abundance of hydrolysates, and the hindrance of intermolecular contact during the reaction. Lower initial molecular weight (low average chain length) makes the mineralization process progress faster [58] . (iii) Structure of BPs: Crystallinity and surface hydrophilicity [10] affect the diffusion of water molecules in BPs, hence the hydrolysis.…”
Section: Factors Affecting Biodegradabilitymentioning
confidence: 99%
“…Both PCL and PHB are examples of biodegradable polymers that decompose effectively in natural settings like aquatic environments, soil, and compost. [17][18][19][20] PCL has variable degradation rates in different environments, including compost and various aquatic habitats. 20 For instance, it was shown that PCL was completely assimilated over a period of six weeks in seawater and after forty-two weeks in natural fresh water.…”
Section: Introductionmentioning
confidence: 99%